The Cytotoxic Activity of Solanum Nigrum Ethanolic Extract on Widr Human Colon Cancer Cells - Maruti, Astrid Ayu; F, Ilham Augusta; Putri, Dyaningtyas D.P.; Hermawan, Adam; Ikawati, Muthiâ (Indonesian Research Gateway, 2011)
Solanum nigrum L. or Leunca in Indonesia has been traditionally used as a herbal plant, which is believed to have anti-tumor properties, although the mechanism for the activity remains unknown. The resecarch aim to examine the cytotoxic effect of the ethanolic extract of Solanum nigrum on WiDr human colon cancer cells. In this study, we prepared an ethanol extract from herb of Solanum nigrum and investigated the mechanism involved in its growth-inhibitory effect on WiDr human colon cancer cells. Herbs of Solanum nigrum dry powder is extracted with 70% ethanol then added into the WiDr cell culture in 96 wells plate in various concentration : 50, 100, 250, and 500 µg/ml. Cytotoxicity of the Solanum nigrum ethanolic extract was analyzed with MTT assay on WiDr human colon cancer cell lines. Results from the MTT assay showed WiDr cells was weakly suppressed in the presence of the extract. The result of the assay also showed a very close correlation between the Solanum nigrum extract concentration and the surviving cell numbers which means the extract caused cell death in a dose-dependent fashion in WiDr cancer cells with the IC50 of 359,23 µg/ml. Collectively, the research suggest further studies to explore other chemopreventive possibilites of Solanum nigrum ethanolic extract.Key words : colon cancer, MTT assay, cytotoxic, WiDr, Solanum nigrum